Prevalence of acute respiratory infections among children under five years of age attending rural health training centre of Era’s Lucknow Medical College and Hospital - Asghar, Syed Abid; Srivastava, Mrinal R.; Srivastava, J. P.; Gupta, Pratibha; Zaidi, Zeashan H. (International Journal Of Community Medicine And Public Health, 2017)
Background: Every year ARI in young children is responsible for an estimated 3.9 million deaths worldwide. About 90 percent deaths are due to Pneumonia which is usually bacterial in origin. By low-cost interventions such as hand washing, breast feeding, accessibility of rapid and attainable methods of early diagnosis of ARI, can help to reduce its burden. Improving the primary medical care services and developing better methods for early detection, treatment and where possible, prevention of acute respiratory infection is the best strategy to control ARI. The aim of the study was to estimate prevalence of ARI among children under-5 years of age attending Rural Health Training Centre of Era’s Lucknow Medical College and Hospital. Methods: The present study was carried out from Nov.2015 to April 2016 covering 305 children below 5 years from RHTC of Era’s Lucknow Medical College and Hospital. Children with acute respiratory infection (ARI) having symptoms like cough, running nose, sore throat, nasal congestion or breathing difficulty were included in the study. Results: Out of 305 children under 5 years, 43 (14%) were diagnosed with ARI. The overall prevalence of ARI was 14% with 95%CI (10.20-18.0). According to social class, prevalence of ARI was higher in low socioeconomic class 42.96%.Statistically no significance between social class and prevalence of ARI was seen with Chi sq test: 0.879, t= 0.928.Overcrowding were present in 33% of cases with 95% CI (17.2-48.80). Inadequate ventilation 48% with 95% CI (31.21-64.79), and uses of smoky chullah 49% with 95% CI (31.21-64.79). Prevalence of ARI was more prevalent in children with malnutrition 52.9%. Statistically high association was seen between ARI status and nutritional status, with Chi squre test:18.3, t≤0.001. Conclusions: The study concludes that malnutrition, low socioeconomic status, poor nutritional status, maternal illiteracy, overcrowding, and inadequate ventilation were the major social and demographic risk factors responsible for ARI in under five children. Minimizing these risk factors and by cost effective interventions one can significantly reduce the prevalence of ARI in the rural community.